1993
DOI: 10.1006/excr.1993.1309
|View full text |Cite
|
Sign up to set email alerts
|

DNA Topoisomerase II Is Not Detectable on Lampbrush Chromosomes but Enriched in the Amplified Nucleoli of Xenopus Oocytes

Abstract: In somatic cells DNA topoisomerase 11 (topo 11) is thought to be involved in the domain organization of the genome by anchoring the basis of chromatin loops to a chromosomal scaffold. Lampbrush chromosomes of amphibian oocytes directly display this radial loop organization in cytological preparations. In order to find out whether topo 11 may play a role in the organization of these meiotic chromosomes, we performed immunofluorescence studies using antibodies against Xenopus topo 11. Our results indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
(55 reference statements)
0
7
1
Order By: Relevance
“…Thus, it is reasonable to expect topo II to be involved in the process of active pol II transcription on the lateral loops of the LBCs. However, immunofluorescence analysis did not reveal direct association of topo II with lateral loops in avian (our data) or in amphibian GVs (Fisher et al 1993;Hock et al 1996). Immunoelectron microscopy studies performed on thin sections of chaffinch GVs showed the presence of topo II in the nucleoplasm.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Thus, it is reasonable to expect topo II to be involved in the process of active pol II transcription on the lateral loops of the LBCs. However, immunofluorescence analysis did not reveal direct association of topo II with lateral loops in avian (our data) or in amphibian GVs (Fisher et al 1993;Hock et al 1996). Immunoelectron microscopy studies performed on thin sections of chaffinch GVs showed the presence of topo II in the nucleoplasm.…”
Section: Discussioncontrasting
confidence: 80%
“…Topoisomerase II was not detectable in other parts of the LBCs (Fisher et al 1993). Because of the morphological resemblance between avian PBs and amphibian axial granules, we used mAb 4A6 to stain GV spreads from both chaffinch and pigeon previtellogenic oocytes.…”
Section: Resultsmentioning
confidence: 99%
“…As for DNA topoisomerase II α, its role as a structural link anchoring the bases of chromatin loops to the nuclear matrix or chromosome scaffold in mammalian cells has been repeatedly proposed (see for example Cockerill and Garrard 1986;Gasser and Laemmli 1986;Adachi et al 1989), even though more recent evidence collected from Xenopus oocytes has challenged such a hypothesis (Fischer et al 1993;Hirano and Mitchison 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to catalytic activity, topoisomerase II may function to anchor chromosomal DNA loops to the nuclear scaffold (8,9); topoisomerase II is a major non-histone protein present in nuclear scaffold fractions (10,11), and DNA sequences that bind preferentially to the nuclear matrix/chromosomal scaffold (MAR/SAR) contain topoisomerase II cleavage consensus (12). In contrast, the role of topoisomerase II in the maintenance of chromosomes was not supported in studies done using Xenopus egg extracts or Xenopus embryos (13,14). Topoisomerase II has been considered as one of the targets for anticancer drugs (15).…”
mentioning
confidence: 99%